Development of Learning-Based Teaching Materials Realistic Mathematics to Improve Elementary Students Mathematics Learning Results Serdang Bedagai - Ramnah Sinaga; Kms. Muhammad Amin Fauzi; Adi Sutopo (SEAN Institute, 2024)
This study aims to describe the validity of teaching materials based on Realistic Mathematics Learning. The research instrument consisted of expert assessment sheets and student learning outcomes tests. The analysis technique uses expert validation and calculates Gain and N-gain with student test results. The results of the study stated that mathematics teaching materials developed based on realistic mathematics learning had a validity value according to material experts of 88.54%, design experts at 87.33%, and linguists at 90.63%. Mathematics teaching materials developed based on realistic mathematics learning have a practicality value based on student assessment of 0.96 so they are very practical to use in the implementation of learning in class V SD Negeri 104335 Marjan Serdang Bedagai Mathematics teaching materials developed have an effectiveness value based on student learning activities, namely how much increasing the effectiveness of student learning by 55.49% to 88.46% with a very effective category. There was an increase in student learning outcomes in fractional arithmetic operations material using realistic mathematics-based teaching materials in which the average pre-test result of 41.73 increased to 87.69, the N-Gain value was 0.79 in the high category and the statistical test score was sig. 0.000< sig. 0.05.